The Performance of Activated Carbon from Used Coffee Grounds Combined with Iron(III) Oxide under UV Light and Ultrasound for Phenol Degradation - Layta Dinira; Barlah Rumhayati; Adam Wiryawan (The Journal of Pure and Applied Chemistry Research, 2021)
Coffee consumption over the past four years has continued to increase the amount of used coffee grounds. Usually, the used coffee grounds are simply thrown away. In fact, it can still be used as other materials that are more efficient and environmentally friendly, such as activated carbon. Activated carbon can be utilized as an adsorbent to adsorb compounds that are carcinogenic and potentially last a long time in the environment, such as phenols. Phenol decomposition through chemical can be carried out by Advanced Oxidation Process (AOP) which utilize hydroxyl radicals. This method used a catalyst such as iron(III) oxide under ultraviolet light. Phenol decomposition can also be carried out using ultrasound. This study presents the performance of the combination of activated carbon-catalyst with ultrasound in phenol decomposition. The results showed that the mass of the composite influenced the 0.1 M phenol degradation by the activated carbon–iron(III) oxide assisted with ultraviolet light, ultrasound, and 0.01 M hydrogen peroxide. for 45 minutes. The best degradation of phenol was obtained when 0.5 g adsorbent was applied with the adsorption capacity of phenol was 704.37 mg/g. The concentration of hydrogen peroxide also affects the decomposition of phenol in solution. From the variation of the hydrogen peroxide solution used (0.01; 0.02; and 0.03 M), the optimal concentration in degrading phenol was 0.01 M with the adsorption capacity of phenol was 393.70 mg/g.